Intermediate Algebra/Systems of Equations By Algebra

Solving Systems of Linear Equations by Using AlgebraEdit

Generally, you're not going to want to solve a system using graphs, simply because it takes too much time. There are two algebraic methods for solving systems of linear equations.


AdditionEdit

The ideal situation for the Addition method (also known as Elimination method) is one in which a variable in the two equations has opposite coefficients. For instance:
6x + 3y = 42
2x - 3y = 22
We would simply add up the values in the two equations, canceling out y in the process.
8x = 64 This is the result of the initial addition.
x = 8 Simplify.
Now, all we have to do is substitute 8 for each occurrence of x,and solve for y.
6(8) + 3y = 42 Substitute the value of x.
48 + 3y = 42 Simplify.
3y = -6 Subtract 48 from each side.
y = -2 Divide each side by 3.

However, even if the variables don't easily cancel out, simply just try with constant multiplications and so on.
3x + 8y = 48
x - 4y = 22
We would simply multiply the second equation throughout by 2 and get:
2x - 8y = 44 Then add up:
x = 4 Substitute:
(8) - 4y = 22
- 4y = 18
y = -\frac{9}{2}

In some occasions, you may need to multiply both sides. For example:

3y + 2x = 5
4y + 3x = 10

In this case, we will multiply the first equation by three and the second equation by two.

9y + 6x = 15
8y + 6x = 20

y=-5

9 \times -5 + 6x = 20
-45 +6x = 20
6x=85
x = 14 \frac {1} {6}

SubstitutionEdit

This is another method to solve a system of linear equations. This is ideal if one of the equations is laid out where one variable has a coefficient of one or negative one.
y = 3x + 1
x + 2y = 16
Here you can simply substitute the first algebraic expression that y equals in to the second.
x + 2(3x + 1) = 16
Now simply slove the problem
x + 6x + 2 = 16
7x + 2 = 16
7x + 2 - 2= 16 -2
\frac{7x}{7}  = \frac{14}{7}
x = 2
Then plug it into the equation you substituted earlier.
y = 3(2) + 1
y = 6 + 1
y = 7
To check your work simply plug both x and y into one part of your system.
x + 2y = 16
(2) + 2(7) = 16
16 = 16 check.


Example where variable is not on one side:

x + y = 9
3x + 5y = 25


Switch first equation so x is on one side

x = 9 - y


Substitute

3(9-y) + 5y = 25


Distribute and solve

27 - 3y + 5y = 25
2y = -2

y = -1
x = 10

Last modified on 13 December 2009, at 18:02